1992
DOI: 10.1123/pes.4.1.36
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Efficiency during Walking in Children and Adults

Abstract: This study compared metabolic, kinematic, and efficiency parameters in 10 boys and 10 men while walking at speeds of similar relative intensities. Heart rate and oxygen consumption were monitored throughout the exercise and a sagittal view of the subject was filmed for biomechanical analysis. Angles of the hip, knee, and ankle changed with an increase in walking speed. There were kinematic differences between children and adults at the hip and knee. Heart rate and oxygen consumption (ml•kg−1•min−1) were greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…However, in children, although there is limited review of this topic, studies by Rowlands et al (29) and Walker et al (33) reported that gender does not affect estimated EE during walking in adolescents, which supports the finding in this study. The gender difference that is apparent in adults, and not children, is potentially related to physiological and biomechanical differences that have not manifested in the prepubescent participants (6,30). A limitation of this study is that the impact of any gender influences on the results could have been better shown with the use of an analysis of covariance, rather than using smaller sample sized groups and reducing statistical power.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, in children, although there is limited review of this topic, studies by Rowlands et al (29) and Walker et al (33) reported that gender does not affect estimated EE during walking in adolescents, which supports the finding in this study. The gender difference that is apparent in adults, and not children, is potentially related to physiological and biomechanical differences that have not manifested in the prepubescent participants (6,30). A limitation of this study is that the impact of any gender influences on the results could have been better shown with the use of an analysis of covariance, rather than using smaller sample sized groups and reducing statistical power.…”
Section: Discussionmentioning
confidence: 93%
“…'overweight' and obese is increasing (4). Walking and running are popular forms of physical activity, especially because they are self-regulated and involve no special skills or facilities (6,26). They use major muscle groups of the body and result in increased EE, which can potentially reduce body fatness (20).…”
mentioning
confidence: 99%
“…Nutritional status analysis is relevant in the functional evaluation of children, since mass gain is associated with an increase in overweight and obesity. This does not necessarily imply higher 6MWT work production, since these conditions lead to worse 6MWT performance for the age group (lower 6MWT distance ) in addition to generating metabolic overload to the individual [1,30]. Compared to adults, the height and weight directly influence the work produced during walking, considering the body's necessary displacement in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to adults, the height and weight directly influence the work produced during walking, considering the body's necessary displacement in the environment. This is particularly applicable to children, who present a higher energy cost per kilogram of body weight per meter of distance traveled [13,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there are many concerns regarding the use of running tests as an indicator of CRF in young children. Performance in the growing years can be compromised in many children due to their relative immaturity from a biomechanical and energy efficiency perspective (Ebbeling et al, 1992), as well as their motivation, especially in girls. However, the easy administration of shuttle-run test and its common use in large-scale studies makes it a valuable tool for studying CRF in youth.…”
Section: Discussionmentioning
confidence: 99%